2020
DOI: 10.3389/fonc.2020.01423
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Early T-Cell Precursor and Non-ETP Subtypes Among 122 Chinese Adults With Acute Lymphoblastic Leukemia

Abstract: Background: Adult T-cell acute lymphoblastic leukemia (T-ALL) is a rare hematological malignancy and significantly linked to poor outcomes. Early T-cell precursor (ETP) leukemia is a unique subtype of TALL. The aim of this study is to compare the differences between ETP and non-ETP ALLs in China. Methods: We retrospectively analyzed the records of 122 adult TALL patients diagnosed and treated at our center between January 2014 and June 2019. All the patients enrolled were categorized into ETP and non-ETP ALL b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 23 publications
8
19
2
Order By: Relevance
“…In this study, patients in CR had a 2‐year OS of 61.7%, and even high‐risk CR patients had a 2‐year OS of 58.7%. This result is similar to that from other reports, supporting a survival benefit for allo‐HSCT in AYA patients with ETP‐ALL 7,10,14 . In fact, the rate of allo‐HSCT was believed to be the main reason for the prognostic variance of patients with the ETP immunophenotype between different studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, patients in CR had a 2‐year OS of 61.7%, and even high‐risk CR patients had a 2‐year OS of 58.7%. This result is similar to that from other reports, supporting a survival benefit for allo‐HSCT in AYA patients with ETP‐ALL 7,10,14 . In fact, the rate of allo‐HSCT was believed to be the main reason for the prognostic variance of patients with the ETP immunophenotype between different studies.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have demonstrated that allo‐HSCT results in superior outcomes compared with chemotherapy alone 12,13 . Most studies show that ETP‐ALL patients also benefit from allo‐HSCT, but the number of published studies is limited and all studies only include a relatively small number of patients 7,10,14 . To date, the largest report has been from GRAALL (Group for Research on Adult Acute Lymphoblastic Leukemia) 7 .…”
Section: Introductionmentioning
confidence: 99%
“…From our T-ALL patients, ETP-ALL represented 12.7%, which agrees with the results of many studies in which ETP-ALL ranged from 9.7% to 20% of their T-ALL cases (43)(44)(45)(46)(47). But a different study in adult Chinese T-ALL patients by Zhang et al, (2020), ETP-ALL was found in 47.3% (48). This variation in frequency may be due to difference in sample size, ethinity and age groups.…”
Section: Monosomysupporting
confidence: 90%
“…Similar results were found in other studies ( 3 , 7 ). However, recently, some studies have found that the prognosis of ETP-ALL was not significantly different from that of typical T-ALL ( 5 , 8 , 9 ). The largest published report on ETP was from Zhang et al., in which 53 ETP-ALL patients were included.…”
Section: Introductionmentioning
confidence: 93%
“…ETP-ALL has been reported in 13~16% of T cell acute lymphoblastic leukemia (T-ALL) cases in children ( 1 , 2 ) and 17~32% in adults ( 3 , 4 ). In China, ETP-ALL accounts for approximately 45% of adult T-ALL ( 5 ). ETP-ALL/LBL has a unique gene mutation expression profile, mainly manifested as a higher incidence of mutations in genes regulating cytokine receptor and RAS signaling, which was similar to the mutational spectrum of myeloid tumors ( 6 ).…”
Section: Introductionmentioning
confidence: 99%